OPTIMIZATION OF PRODUCTION COSTS WITH SIMPLEX METHOD - Firmansyah, Firmansyah; Panjaitan, Dedy Juliandri; Salayan, Madyunus; Silalahi, Alistraja Dison (Universitas Negeri Medan, 2020)
One of the problems in the company is my resource limitation, the time of production and the tools used in the production process. Companies in making decisions in production planning in the presence of these limitations, should seek to maximize the profit generated. However, in the production process a production planning reference is required to maximize the results obtained and minimize the production costs used. To solve the problem, needed a problem solving tool that is linear program using simplex method. Simplex method is one of the methods of linear program in solving the problem of more than two variables that can be applied into everyday life and can be used in production process planning. With one of the ultimate goal is the achievement of the optimum value with the constraints of limited resources. The results of the simplex method have decreased costs incurred less than the usual costs incurred every month and the results obtained using the simplex method can be used as a reference in making decisions to get optimal results on production costs in the company.